T.D. Jakes : America's New Preacher. - Lee, Shayne (NYU Press, 2007)
T.D. Jakes has emerged as one of the most prolific spiritual leaders of our time. He is pastor of one of the largest churches in the country, CEO of a multimillion dollar empire, the host of a television program, author of a dozen bestsellers, and the producer of two Grammy Award-nominated CDs and three critically acclaimed plays. In 2001 Time magazine featured Jakes on the cover and asked: Is Jakes the next Billy Graham. T.D. Jakes draws on extensive research, including interviews with numerous friends and colleagues of Jakes, to examine both Jakes's rise to prominence and proliferation of a.